Psychological distress Management in Iranian emergency prehospital providers: A Qualitative study - Maryam Azizi; Reza Bidaki; Abbas Ebadi; Abbas Ostadtaghizadeh; Abbasali Dehghani Tafti; Ahmad Hajebi; Azizeh Alizadeh; Hamid Reza Khankeh (Wolters Kluwer Medknow Publications, 2021)
INTRODUCTION: Emergency prehospital providers (EPHP) who are constantly providing medical care in threatening conditions are more at risk of displaying psychological distress presentations in disaster situations. Problem-solving strategies are essential for effective and efficient management of event position. Therefore, the present study aimed to explore psychological distress promotion in Iranian EPHP. MATERIALS AND METHODS: A qualitative content analysis study was conducted based on 24 semi-structured interviews. A purposeful sampling method was applied until reaching data saturation. Interviews were transcribed verbatim, and then, data condensing, labeling, coding, and defining categories were performed by the qualitative content analysis recommended by the Landman and Graneheim approach. RESULTS: Based on the experience of study participants, two main themes with six categories developed. The main themes included emotion-based management and problem-based management when confronting with incidence scene. CONCLUSION: The main problems of EPHP in confronting with incidence and disasters scenes are psychological distress which some rescuers have emotional reactions while some others who are more resilience and experience manage this problem in the form of problem-based approach. It is recommended these practical strategies to be taught to less experienced rescuers for avoiding emotional-based reactions and better management of disaster scene.